Indonesia’s National Economic Recovery Through the Convenience of Companies Establishing of Micro and Small Enterprises in the Job Creation Act - Putu Ayu Sriasih Wesna (Publikasi Indonesia, 2022)
Since the establishment of the Covid-19 virus as a pandemic, it has brought a huge downturn in the national and global economy. Various efforts have been made by the Indonesian government to increase economic growth so that Indonesia can avoid the economic crisis. The Indonesian government in its various policies has created pro-community programs to accelerate economic recovery. The aim is to provide convenience in the establishment of a limited liability company which originally had to be established by at least two founders based on an agreement, so that the establishment of a limited liability company called a limited liability company can now be established by one person. by simply making a statement. The technique used in this research is a systematic and interpretive descriptive-analytical technique, which describes the strengths and weaknesses of a legal product being analyzed, and tries to find a relationship between the formulation of a legal concept or legal argument between the articles contained. in the same legal product. Based on the research results, the government encourages the development of micro and small businesses as an effort to encourage the people's economy which can accelerate the recovery of the national economy with the enactment of Law Number 11 of 2020 concerning Job Creation.